Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Atlantic)--Blue crab - Van den Avyle, Michael J. (U.S. Departmen of the Interior, 1984)
U.S. Fish Wildl. Serv. FWS/OBS-82/11.19